Patiromer Acetate Induced Hypercalcemia: An Unreported Adverse Effect - Shreeyukta Bhattarai; Stephen Pupillo; Gulshan Man Singh Dangol; Erdal Sarac (Case Reports in Nephrology)
Hyperkalemia, a potential life threating condition, is a commonly encountered problem in chronic kidney disease (CKD) patients. Patiromer acetate, a nonabsorbable cation exchange polymer, is a gastrointestinal agent for chronic therapy in patients with persistent hyperkalemia. Patiromer is generally well tolerated in patients; common side effects are gastrointestinal, such as diarrhea, constipation, flatulence, and vomiting. Hypercalcemia, although a theoretical possibility, has not been reported in any major clinical trials. We present a case of hypercalcemia associated with patiromer acetate used for treatment of hyperkalemia in a stage IV CKD patient. Clinicians should be aware of the possibility of hypercalcemia while taking patiromer.